Developing Oral Production through the Use of Synchronous and Asynchronous Computer-Mediated Communication (CMC) As a Way to Improve Speaking Competences in the Michigan Test in Modern Languages Students at the University of Quindío. (2018)
The aim of this paper is to comprehend the outcome of Computer-mediated Communication (CMC) on ESL oral production in 10 students from 3rd and 4th courses of Modern Languages at the University of Quindío. These students should have B1 level of English established by CEFR to pass the Michigan Test (a requirement to continue their academicals studies). It used task based activities through WhatsApp and Skype platforms, from a sociocultural perspective, to enhance oral production skills through. The method used for collecting data in this analysis was qualitative: through a series of three series of 20 min. interventions among tutors abroad and students In which only they used only English as the mean of communication. The material was used by tutors to guide students to the topics. The lessons involved the use of synchronous communication like video calls, text messaging, and voice notes in which participants were connected at the same time; and the use of Asynchronous communication like video links or texts in which participants communicate without being connected at the same time. In the first stage, students answered an interview to obtain qualitative data in order to design the proper contents before starting the lessons. Once the lessons took place, all the students were required to fill a questionnaire which tested their level in quantitative language units. During the lessons, students were asked about sociocultural topics and involved into 20 minutes conversation to explore their oral production. Tutors recorded four minutes voice notes at the end of each lessons in which it was determine the students‟ performance in the lesson same as the perception about CMC use for this purpose besides. After the last interactions, students were asked too about their impressions of their participation. Therefore, this study follows a qualitative design where qualitative and quantitative methods are employed. Results show whatsApp and Skype succeeded to lead guided activities as video calls, calls, sharing files (SCMC) improving oral production in ESL; and posting activities (ACMC). WhatsApp and Skype were easy tools to use and innovative despite of some occasional signal failures. Tutors affirmed students became more fluent due to the predominant exposition to oral production.